Proteomic Assessment of iTRAQ-Based NaoMaiTong in the Treatment of Ischemic Stroke in Rats. (15th May 2019) - Li, Kening; Xian, Minghua; Chen, Chi; Liang, Shengwang; Chen, Lei; Wang, Shumei
Abstract : Background . NaoMaiTong (NMT) is widely used in the treatment of cerebral ischemia but the molecular details of its beneficial effects remain poorly characterized. Materials and Methods . In this study, we used iTRAQ using 2D LC-MS/MS technology to investigate the cellular mechanisms governing the protective effects of NMT. The transient middle cerebral artery occlusion (MCAO) rat model was established and evaluated. The degree of cerebral ischemia was assessed through scoring for nerve injury symptoms and through the assessment of the areas of cerebral infarction. Brain tissues were subjected to analysis by iTRAQ. High-pH HPLC and RSLC-MS/MS analysis were performed to detect differentially expressed proteins (DEPs) between the treatment groups (Sham, MCAO, and NMT). Bioinformatics were employed for data analysis and DEPs were validated by western blot. Results . The results showed that NMT offers protection to the neurological damage caused by MCAO and was found to reduce the areas of cerebral infarction. We detected 3216 DEPs via mass spectrometry. Of these proteins, 21 displayed altered expression following NMT intervention. These included DEPs involved in translation, cell cycle regulation, cellular nitrogen metabolism, and stress responses. Pathway analysis revealed seven key DEPs that were enriched in ribosomal synthesis pathways, tight junction formation, and regulation of the actin cytoskeleton. According to protein-protein interaction analysis, RPL17, Tuba, and Rac1 were affected by NMT treatment, which was validated by western blot analysis. Discussion . We therefore identify new pharmacodynamic mechanisms of NMT for the prevention and treatment of ischemic stroke. These DEPs reveal new targets to prevent ischemic stroke induced neuronal damage.